Memberitakan Injil Tanpa Upah berdasarkan 1 Korintus 9:18 bagi Pelayanan Hamba Tuhan - Yohanes Telaumbanua (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2023)
Serving God is a special calling for everyone. The response to the call is strongly influenced by the motivation of each individual. The motivation possessed by a person determines the goals to be achieved while serving. It cannot be denied that in this demanding era, every servant of God has a competitive lifestyle, namely: not wanting to be difficult, not wanting to be out of date. The motivation possessed by a person determines the goals to be achieved while serving. then the ministry of God's servant changed direction and motivation to serve. To overcome this problem, the author raises a Bible character named Paul, who is so persistent in serving God, that he says